Justice is an option : a democratic theory of finance for the twe nty-first century - Meister, Robert, 1947- (Chicago : The University of Chicago Press, 2021)
"In Justice as an Option, Robert Meister returns to the spirit of Ma rx to diagnose our current age of finance. Instead of closing our eyes to the political economic realities of our era and dreaming of a return to a more equitable time, we need to grapple with them head on. Meiste r does just that, asking if the very tools of finance that have created our vastly unequal world can be made to serve justice and equality. Bo ldly disproving the perceived inaccessibility of contemporary capitalis m as a target of collective action, Meister formulates a democratic fin ancial theory for the twenty-first century. Ranging between political p hilosophy, Marxism, and contemporary politics, Justice as an Option is an invigorating first page of a new-and sorely needed-leftist playbook" --
Finance and Marx -- Market liquidity and financial power -- Trauma o r injustice -- Is justice an option? -- Justice as an option -- Can cap italism short iItself? -- Funding justice -- Conclusion -- Afterword: S pring 2020.
Includes bibliographical references (p.209-279) and index.
Keywords: Finance, Public -- United States; Debt -- Political aspects -- United States; Liquidity (Economics); Social justice; Marxian economics